Acute Toxicity and Antifungal Effects of Acacia ataxacantha - LAGNIKA, LATIFOU (My University, 2015)
The present study aimed to evaluate the antifungal activities of Acacia ataxacantha against six strains of Aspergillus and the acute toxicity of hydroalcoholic extract in rat models. Five extracts including hexane, dichloromethane, ethyl acetate, methanol and mixture of water/ethanol of A. ataxacantha’s barks were evaluated against six Aspergillus strains using agar diffusion method and counting of number fungal spores. Oral acute toxicity at a dose of 2000 mg/kg was conducted as per Organization for Economic Co-operation and Development (OECD) 423 guidelines. Results obtained showed that all the extracts inhibited mycelial growth and sporulation of fungi with percentages of inhibition ranging from 5.37- 53.02% and 33.77 to 99.70% respectively. The antifungal activity of the extracts at the same concentration is more marked on the sporulation of fungi. Ethyl acetate and dichloromethane extracts exhibited the most significant antifungal activity. In the acute toxicity evaluation, all animals were physically active and no deaths of rats were observed during the test. No significant change was observed in body weight, haematological and biochemical parameters of treated rats compared with controls. The histopatological analysis of liver and kidney showed normal architecture suggesting no morphological disturbances. The overall finding of this study suggests that A. ataxacantha inhibited the mycelial growth and sporulation of Aspergillus strains. Equally, hydroalcoholic extract of this plant is non-toxic up to 2000 mg/kg body weight. Thus, A. ataxacantha could be used as an antifungal.
Keywords: Acacia ataxacantha bark; Aspergillus; antifungal activity; acute toxicity.